Kemenarikan Pemilihan Kata Pada Iklan Online Shop Aplikasi Shopee Analisis Wacana Persuasi - Muhammad Zukhruf Fikri Al Ayubi; Heny Sulistyowati (Departement of Mathematics Education, 2023)
The marketing tool used to help sell goods is commonly called advertising. Advertising serves to provide information, both services, ideas and ideas that are solicitation or persuasive. Advertisers can attract potential customers by using persuasion strategies that will be discussed in this analysis. The source of the data in this study is a piece of advertising discourse. Online advertising discourse on the Shopee application is the data used in this study. The data is in the form of sentences with word choices that attract buyers. The data collection step uses the observation method or the listening method, namely listening to the use of language in advertising discourse. Researchers select data according to research needs. The data analysis used in this study is an interactive model analysis. Interactive analysis basically involves three components, namely, (1) data collection, (2) data reduction, (3) data presentation. The results of the study show that there are two ways advertisers persuade potential customers, namely implicit persuasion and explicit persuasion.